2004
DOI: 10.1213/01.ane.0000115147.14626.c5
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Sensory Dysfunction 6 to 12 Months After Inguinal Herniotomy

Abstract: Inguinal hernia repair is associated with a 5%-30% incidence of chronic pain, but the pathogenesis remains unknown. We therefore evaluated pain and sensory dysfunction by quantitative sensory testing 6-12 mo after open hemiorrhaphy. Before sensory testing, all patients (n = 72) completed a short-form McGill Pain Questionnaire and a functional impairment questionnaire. Sensory dysfunction in the incisional area was evaluated by quantification of thermal and mechanical thresholds, by mechanical pain responses (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 22 publications
7
98
0
7
Order By: Relevance
“…A neuropathic pain component in PIPP 4,5 is corroborated in the current study by baseline S-LANSS scores suggesting pain of predominantly neuropathic origin in 76% of patients. The study did not show significant differences between lidocaine and placebo patches, for the primary outcome parameter, pain relief.…”
Section: Discussionsupporting
confidence: 83%
“…A neuropathic pain component in PIPP 4,5 is corroborated in the current study by baseline S-LANSS scores suggesting pain of predominantly neuropathic origin in 76% of patients. The study did not show significant differences between lidocaine and placebo patches, for the primary outcome parameter, pain relief.…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of chronic pain following repair with use of a mesh, like the Lichtenstein technique, varies between 5% and 54% (Poobalan 2003;Loos 2007a;Kehlet 2008), with a pooled incidence of 11% to 16.8% (Perkins 2000;Nienhuijs 2007;Simons 2009;Koning 2013). Some 2% to 6% of patients experience significant restrictions in social and daily activities as a consequence of CPIP, leading to an impairment of health status or 'quality of life' (QoL) (Callesen 1999;Poobalan 2001;Bozuk 2003;Aasvang 2005a).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…18,19 In a comparable study design no significantly lower pain scores were reported when a mesh was fixated with staples instead of sutures. 20 The postoperative interval to pain assessment influences the outcome. Lower pain levels are found when followup is longer.…”
Section: Discussionmentioning
confidence: 99%